Global perspectives on interventions in forensic therapeutic communities: a practitioner's guide - Shuker, Richard; Akerman, Geraldine (Issues in forensic psychology, 2022)
"Global Perspectives on Interventions in Forensic Therapeutic Communities: A Practitioner's Guide explores the validity and effectiveness of secure settings as therapeutic communities (TCs). Rooted in practice, this book examines the transferability of approaches within international TCs to other forensic settings, while considering how the environment contributes to effectiveness. In this volume, Akerman and Shuker bring together leading clinicians from across the world to offer insight into critical topics, including the impact of gang membership on therapeutic process and the community, how core creative therapies are integrated, and how the model is applied in international settings and across varied contexts. Leading clinicians draw on rare reports and papers to explain the therapeutic community model while keeping the diverse contexts within which it is practiced in mind. The book provides a much-needed global perspective on the diverse role TCs have across forensic services This ground-breaking book is valuable reading for forensic and clinical psychologists, counsellors, social workers, and psychiatrists working in secure prison or rehabilitation settings, as well as students in these fields"--